ORGANIZING THE REGIME OF WORK AND REST OF DRIVERS ON MOUNTAIN ROADS - Moldaliev, Egenberdi; Atabekov, Kalmamat; Mambetalieva, Kunduz; Troyanovskaya, Irina; Voinash, Sergey; Zagidullin, Ramil; Sabitov, Linar (Journal of Applied Engineering Science, 2023)
Mountain roads in Kyrgyzstan are characterized a large difference in altitude above sea level. Above 2,000 meters above sea level, drivers develop symptoms of altitude sickness. The aim of the study is to study the effect of atmospheric pressure on the body of a vehicle driver in mountainous conditions. The Bishkek-Naryn-Torugart international highway was chosen as an object. Control point No. 1 is located on the Torugart pass near the border with China (altitude is 3752 meters above sea level). Checkpoint No. 2 is located near the village of At-Bashy (altitude above sea level is 2046 meters). Control point No. 3 is located near the village of Kemin (altitude 1120 meters above sea level). The results of the study showed that blood pressure indicators change along the considered route depending on the height above sea level. For example, pressure indicators of 140-159 / 90-99 were observed in 24% of drivers at point No. 1, 19% at point No. 2 and only 5% at point No. 3. Blood pressure 160-179 / 100-109 (moderate hypertension) was observed in 7% of drivers in point 1 and in 5% of drivers in point 2. The main reason for the increase in pressure was a violation of the mode of work and rest of drivers. As a result, standards for the work of drivers of international road transport in high altitude conditions were developed and measures were proposed for the mandatory organization of rest places for drivers on the Bishkek-Naryn-Torugart road.